THE IMPACT OF COMPANY CHARACTERISTICS TO INCREASE COMPANY VALUE WITH CORPORATE RISK MANAGEMENT AS MEDIATION IN COMPANIES LISTED ON THE IDX IN 2016-2020 - Sarsiti; Juni Trisnowati; Erni Widiastuti (International Journal of Social Science, 2024)
The research objectives are based on the research of Bohnert, A., et al., 2023 and Nguyen, Lan, et al. 2021, namely to examine the impact of size and leverage on firm value with enterprise risk management (ERM) as mediation. The sample technique used is purposive sampling, and the data used is secondary data from annual financial report data listed on the Indonesia Stock Exchange from 2016-2020, totaling 15 property and real estate industry sectors. Path analysis and the Sobel test are used in the data analysis technique. The findings indicated that: (1) firm size has a negative and insignificant impact on ERM; (2) leverage has a positive and insignificant impact on ERM; (3) firm value is positively but insignificantly impacted by company size and leverage; and (4) ERM has a negative and insignificant impact on firm value. (5) The impact of firm size and leverage on firm value is not mediated by ERM